Robust sliding mode controller design for orbital payload deploying spacecraft - Platanitis, Konstantinos; Felicetti, Leonard; Upadhyay, Saurabh; Capicchiano, Leonardo (Council of European Aerospace Societies (CEAS), 2024)
This work demonstrates the feasibility of usage of a sliding mode controller in the case of orbital payload deployers. The proposed control law suggested herein allows for disturbance rejection during the payload deployment phase, as well as provide a basis for angular rate tracking purposes. The stability of the control law is determined by Lyapunov theory, and realistic spacecraft simulations have been created to verify the robustness in the presence of disturbances as well as the general tracking capabilities.
Keywords: Sliding mode control; Attitude control; Oribtal payload deployer